A Multifunctional Polymer as an Interfacial Layer for Efficient and Stable Perovskite Solar Cells. Issue 2 (7th December 2022) - Zhang, Bingqian; Chen, Chen; Wang, Xianzhao; Du, Xiaofan; Liu, Dachang; Sun, Xiuhong; Li, Zhipeng; Hao, Lianzheng; Gao, Caiyun; Li, Yimeng; Shao, Zhipeng; Wang, Xiao; et al.
Abstract: Metal‐cation defects and halogen‐anion defects in perovskite films are critical to the efficiency and stability of perovskite solar cells (PSCs). In this work, a random polymer, poly(methyl methacrylate‐ co ‐acrylamide) (PMMA‐AM), was synthesized to serve as an interfacial passivation layer for synergistically passivating the under‐coordinated Pb 2+ and anchor the I ‐ of the [PbI6 ] 4− octahedron. Additionally, the interfacial PMMA‐AM passivation layer cannot be destroyed during the hole transport layer deposition because of its low solubility in chlorobenzene. This passivation leads to an enhancement in the open‐circuit voltage from 1.12 to 1.22 V and improved stability in solar cell devices, with the device maintaining 95 % of the initial power conversion efficiency (PCE) over 1000 h of maximum power point tracking. Additionally, a large‐area solar cell module was fabricated using this approach, achieving a PCE of 20.64 %. Abstract : A novel multifunctional polymer, poly(methyl methacrylate‐ co ‐acrylamide), was designed and utilized to synergistically passivate the under‐coordinated Pb 2+ and anchor the I ‐ of the [PbI6 ] 4− octahedron on the surface of a perovskite film. This passivation leads to an enhancement in the open‐circuit voltage from 1.12 to 1.22 V and improved stability in solar cell devices, with the device maintaining 95 % of the initial power conversion efficiency (PCE) over 1000 h of maximum power point tracking. Additionally, a large‐area solar cell device was fabricated using this approach, achieving a PCE of 20.64 %.